Auranofin coated catheters inhibit bacterial and fungal biofilms in a murine subcutaneous model - Felix, LewisOscar; Whitely, Cutler; Tharmalingam, Nagendran; Mishra, Biswajit; Vera-Gonzalez, Noel; Mylonakis, Eleftherios; Shukla, Anita; Fuchs, Beth Burgwyn (Frontiers in Cellular and Infection Microbiology, 2023)
Microbe entry through catheter ports can lead to biofilm accumulation and complications from catheter-related bloodstream infection and ultimately require antimicrobial treatment and catheter replacement. Although strides have been made with microbial prevention by applying standardized antiseptic techniques during catheter implantation, both bacterial and fungal microbes can present health risks to already sick individuals. To reduce microbial adhesion, murine and human catheters were coated with polyurethane and auranofin using a dip coating method and compared to non-coated materials. Upon passage of fluid through the coated material in vitro, flow dynamics were not impacted. The unique antimicrobial properties of the coating material auranofin has shown inhibitory activity against bacteria such as Staphylococcus aureus and fungi such as Candida albicans. Auranofin coating on catheters at 10mg/mL reduced C. albicans accumulation in vitro from 2.0 x 108 to 7.8 x 105 CFU for mouse catheters and from 1.6 x 107 to 2.8 x 106 for human catheters, showing an impact to mature biofilms. Assessment of a dual microbe biofilm on auranofin-coated catheters resulted in a 2-log reduction in S. aureus and a 3-log reduction in C. albicans compared to uncoated catheters. In vivo assessment in a murine subcutaneous model demonstrated that catheters coated with 10 mg/mL auranofin reduced independent S. aureus and C. albicans accumulation by 4-log and 1-log, respectively, compared to non-coated catheters. In conclusion, the auranofin-coated catheters demonstrate proficiency at inhibiting multiple pathogens by decreasing S. aureus and C. albicans biofilm accumulation.